Post-exercise hypotension phenomenon in elderly after aerobic exercise - Agha Bhargah; Made Muliarta; I Putu Yuda Prabawa; Ida Bagus Amertha Putra Manuaba; Varennia Bhargah (Journal of Global Pharma Technology, 2018)
Post-exercise hypotension (PEH) which means the occurrence of changes in blood pressure after a physical exercise to a lower blood pressure level after the start of physical exercise. The incidence of PEH can be concluded as a benefit when viewed regarding people who experience a state of hypertension, but if in people with normal blood pressure circumstances can cause the risk of a state of hypotension. The purpose of this study was to determine the magnitude of the decrease in post-exercise hypotension in elderly. Study model using a quasi-experimental model with pre-test and post-test group design involving 28 elderly as a research subject. Aerobic exercise in this study was performed through a healthy heart gymnastics exercise with a duration of 45 minutes. Blood pressure measurements were performed before exercise (baseline value), immediately after exercise, 15 minutes, 30 minutes, 45 minutes, and 60 minutes after exercise was done. Statistical analysis using normality and homogeneity test, ANOVA test, and paired sample t-test to compare differences in blood pressure parameter between period of measurement. There are differences in systolic, diastolic, and Mean Arterial Pressure (MAP) blood pressure between time measurements (p<0.001). The systolic blood pressure was significantly lower at 60 minutes post exercise (121.96±1.43 mmHg) compared with baseline (141.35 ± 8.76) (p<0.001). Diastolic blood pressure was significantly lower at 60 minutes post exercise (121.96 ±1.43 mmHg) compared with baseline (91.75 ± 1.48) (p<0.001). MAP was significantly lower at 60 minutes post exercise (93.89 ± 1.15 mmHg) compared with baseline (108.39±1.34) (p<0.001). Aerobic exercise through a healthy heart gymnastics session on elderly provides a post-exercise hypotension phenomenon. The lowest reduction of blood pressure was found at 60 minutes after aerobic exercise.Keywords: Systolic, Blood Pressure, Hypotension, Diastolic.